2023
DOI: 10.21037/qims-22-599
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics-based intracranial thrombus features on preoperative noncontrast CT predicts successful recanalization of mechanical thrombectomy in acute ischemic stroke

Abstract: Background: To evaluate the predictive value of radiomics features extracted from the thrombus on preoperative computed tomography images to identify successful recanalization after stent retrieve (SR) treatment in patients with acute ischemic stroke (AIS). Methods: Two hundred fifty-six patients newly diagnosed AIS between March 2017 and September 2020 from two institutes, including the first affiliated hospital of Soochow university (institute I) and Northern Jiangsu People's hospital (institute II), were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Notably, 11 of these studies performed a comparation between models using only clinical features and models incorporating radiomics features. While 4 of these studies ( 41 43 , 46 ) did not observe a significant difference in predictive performance, the remaining 7 ( 13 , 38 , 39 , 44 , 47 49 ) demonstrated that the inclusion of radiomics significantly improved the predictive ability for AIS prognosis. Moreover, among these 7 studies, 3 ( 38 , 39 , 44 ) directly compared the performance of the radiomics model with the clinical model, and all found that the radiomics model was superior.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Notably, 11 of these studies performed a comparation between models using only clinical features and models incorporating radiomics features. While 4 of these studies ( 41 43 , 46 ) did not observe a significant difference in predictive performance, the remaining 7 ( 13 , 38 , 39 , 44 , 47 49 ) demonstrated that the inclusion of radiomics significantly improved the predictive ability for AIS prognosis. Moreover, among these 7 studies, 3 ( 38 , 39 , 44 ) directly compared the performance of the radiomics model with the clinical model, and all found that the radiomics model was superior.…”
Section: Resultsmentioning
confidence: 96%
“…Within these studies, ten are dedicated to predicting long-term prognosis, five focus on reperfusion ( 37 , 40 , 41 , 43 , 51 ), and one addresses both aspects ( 42 ). For long-term prognosis, assessment of the mRS spanned a follow-up period of 3–12 months, while assessments of the NIHSS occurred at discharge or on day 7.…”
Section: Resultsmentioning
confidence: 99%
“…al. [ 13 ] on the radiomics features of thrombi in AIS patients proves that some features have a significant predictive power in the outcome of thrombectomy procedures. Out of all the parameters determined in their study, we identify ShortRunLowGrayLevelEmphasis ( p = 0.0016, AUC = 0.813, Sensitivity 81.8%, Specificity 83.3%) and LargeAreaHighGrayLevelEmphasis ( p = 0.037, AUC = 0.737, Sensitivity 50%, Specificity 99.4%) as predictors for the outcome of mechanical thrombectomy procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, radiomics can be harnessed for predictive modelling, where the extracted features are correlated with clinical outcomes. This enhances the prognostic stratification and helps tailor patient-specific interventions, thereby optimizing stroke management [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“… 37 Many investigations have highlighted the potential of combining radiomic and clinical data features into clinical prediction models, which may allow the precise prediction of patients who are likely to have favorable reperfusion outcomes. 38 40 …”
Section: Application Of Imaging Radiomics In Ischemic Cerebrovascular...mentioning
confidence: 99%